Age as a Confounding Factor for the Accurate Non-Invasive Diagnosis of Advanced NAFLD Fibrosis - McPherson, Stuart; Hardy, Tim; Dufour, Jean-Francois; Petta, Salvatore; Romero-Gomez, Manuel; Allison, Mike; Oliveira, Claudia P; Francque, Sven; Van Gaal, Luc; Schattenberg, Jörn M; Tiniakos, Dina; Burt, Alastair; et al. (The American journal of gastroenterology, 2017)
Non-invasive fibrosis scores are widely used to identify/exclude advanced fibrosis in patients with non-alcoholic fatty liver disease (NAFLD). However, these scores were principally developed and validated in patients aged between 35 and 65 years of age. The objective of this study was to assess the effect of age on the performance of non-invasive fibrosis tests in NAFLD. Patients were recruited from European specialist hepatology clinics. The cohort was divided into five age-based groups: ≤35 (n=74), 36-45 (n=96), 46-55 (n=197), 56-64 (n=191), and ≥65 years (n=76), and the performance of the aspartate aminotransferase (AST)/alanine transaminase (ALT) ratio, fibrosis 4 (FIB-4), and NAFLD fibrosis score (NFS) for advanced fibrosis (stage F3-F4) for each group was assessed using liver biopsy as the standard. Six hundred and thirty-four patients were included. The diagnostic accuracy of the AST/ALT ratio was lower than NFS and FIB-4 in all the age groups. The AST/ALT ratio, NFS, and FIB-4 score performed poorly for a diagnosis of advanced fibrosis in those aged ≤35 years (area under the receiver operating characteristic curves (AUROCs 0.52, 0.52, and 0.60, respectively). For all groups >35 years, AUROCs for advanced fibrosis were similar for the NFS and FIB-4 score (range 0.77-0.84). However, the specificity for advanced fibrosis using the FIB-4 and NFS declined with age, becoming unacceptably low in those aged ≥65 years (35% for FIB-4 and 20% for NFS). New cutoffs were derived (and validated) for those aged ≥65 years, which improved specificity to 70% without adversely affecting sensitivity (FIB-4 2.0, sensitivity 77%; NFS 0.12, sensitivity 80%). The NFS and FIB-4 scores have similar accuracy for advanced fibrosis in patients aged >35 years. However, the specificity for advanced fibrosis is unacceptably low in patients aged ≥65 years, resulting in a high false positive rate. New thresholds for use in patients aged ≥65 years are proposed to address this issue.